Conducting a VR Clinical Trial in the Era of COVID-19 - Stradford, Joy; Sakhare, Ashwin; Ravichandran, Roshan; Schroeder, E. Todd; Michener, Lori A.; Pa, Judy (Frontiers in Virtual Reality, 2021)
The outbreak of severe acute respiratory syndrome coronavirus 2, also known as Coronavirus Disease 2019 (COVID-19) sparked a global public health pandemic that has impacted every aspect of daily life (Ayittey et al., 2020; Stawicki et al., 2020). Medical research was affected, and many clinical trials were halted to minimize COVID-19 transmission risk and spread while the world navigated this novel virus (Sathian et al., 2020). Here we describe the relaunch of our virtual reality (VR) pilot clinical trial that uses an in-lab brain and body training program to promote brain health in mid-to-late life older adults, in the era of COVID-19. This case series includes five healthy female participants between 51-76 years of age, a subset of a larger VR pilot clinical trial that started pre-pandemic. We developed a revised study protocol based on the Center for Disease Control and World Health Organization guidelines to help manage the spread of COVID-19. Since the limited resumption of clinical trials at our institution in August 2020, we successfully completed over 200 in-lab virtual reality training sessions using our revised protocol. During this time, none of the five participants or three study staff reported any COVID-19 symptoms or reported a positive COVID-19 test. More than 40 voluntary COVID-19 tests were completed by our study staff over the last six months. All participants rated our safety protocol as very satisfied or extremely satisfied and that they would be very likely or extremely likely to participate in a VR clinical trial during the pandemic. Based on these findings, we suggest that continued VR clinical trial research during the COVID-19 pandemic is achievable and can be safely resumed if specific safety protocols are in place to mitigate the risk of exposure and spread of COVID-19.